2009
DOI: 10.1177/1010539509331786
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity Among Adolescents (10 to 14 Years) in Kuwait

Abstract: The purpose of this cross-sectional study was to find out the prevalence of obesity and overweight among intermediate school adolescents aged 10 to 14 years. The study comprised a multistage stratified random sample that included 5402 children (2657 males and 2745 females). They represent 12.7% of the total number of children between 10 and 14 years during the educational year 2005-2006. The weights and heights of adolescents were measured, from which the body mass index (BMI) was calculated, which is the weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
76
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 26 publications
7
76
5
Order By: Relevance
“…On the other hand, our results were much lower than [13] in Kuwait. Concerning the prevalence of obesity, our results were in agreement with [10] [11], but it was higher than [9] [12] and [13]. Apart from Kuwait, all of these studies showed nearly similar rates of overweight, while the prevalence of obesity showed marked variation.…”
Section: Discussioncontrasting
confidence: 52%
“…On the other hand, our results were much lower than [13] in Kuwait. Concerning the prevalence of obesity, our results were in agreement with [10] [11], but it was higher than [9] [12] and [13]. Apart from Kuwait, all of these studies showed nearly similar rates of overweight, while the prevalence of obesity showed marked variation.…”
Section: Discussioncontrasting
confidence: 52%
“…Kuwait has the highest childhood overweight problem among the Gulf countries and obesity is reportedly on the rise (2) . El-Bayoumy et al (8) reported that 30?7 % and 14?6 % of children between the ages of 10 and 14 years were overweight and obese, respectively; while 43?3 % and 21?3 % of children between 14 and 19 years of age were overweight and obese, respectively (7) .Before the discovery of oil, Kuwait's food supply was limited. Available foods consisted mainly of rice, dates, seafood, camel milk, sheep and goat meat and their by-products (9) .…”
mentioning
confidence: 99%
“…On account of lifestyle changes associated with the transition in nutrition in the Arabian Gulf, resulting principally from rising incomes associated with the discovery and production of oil over the past few decades, obesity has increased dramatically (9,10) . El Bayoumy et al (11) found that the overall prevalence of overweight and *Corresponding author: Email bojack@umd.edu r The Authors 2010 obesity among men was 29?3 % and 14?9 %, respectively, (P , 0?001) and the prevalence of overweight and obesity among women was 32?1 % and 14?2 %, respectively (P , 0?001). Studies have shown that with new affluence has come increased availability of fast-food restaurants and ready availability of other semi-fast food establishments in all Gulf countries, including Kuwait (9,12) .…”
mentioning
confidence: 99%